2014
DOI: 10.1158/1078-0432.ccr-13-3292
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Aldehyde Dehydrogenase 1A3 for the Maintenance of Non–Small Cell Lung Cancer Stem Cells Is Associated with the STAT3 Pathway

Abstract: Purpose Lung cancer stem cells (CSCs) with elevated aldehyde dehydrogenase (ALDH) activity are self-renewing, clonogenic and tumorigenic. The purpose of our study is to elucidate the mechanisms by which lung CSCs are regulated. Experimental Design A genome-wide gene expression analysis was performed to identify genes differentially expressed in the ALDH+ vs. ALDH− cells. RT-PCR, western blot and Aldefluor assay were used to validate identified genes. To explore the function in CSCs we manipulated their expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 43 publications
(51 reference statements)
3
143
0
2
Order By: Relevance
“…In addition, they also found that ALDH1B1 is dramatically upregulated in human colonic adenocarcinoma and therefore considering it as a potential biomarker for human colon cancer (23). Although high ALDH1A3 levels have already been detected in more aggressive forms of breast, bladder, and lung cancers (18,22,26), this work is nevertheless the first, to our knowledge, to report that ALDH1A3 is the main ALDH isoenzyme in intrahepatic cholangiocarcinoma. More importantly, we also found that ALDH1A3 is a critical prognostic factor in 77 patients with intrahepatic cholangiocarcinoma who received hepatectomies among several clinicopathologic features.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, they also found that ALDH1B1 is dramatically upregulated in human colonic adenocarcinoma and therefore considering it as a potential biomarker for human colon cancer (23). Although high ALDH1A3 levels have already been detected in more aggressive forms of breast, bladder, and lung cancers (18,22,26), this work is nevertheless the first, to our knowledge, to report that ALDH1A3 is the main ALDH isoenzyme in intrahepatic cholangiocarcinoma. More importantly, we also found that ALDH1A3 is a critical prognostic factor in 77 patients with intrahepatic cholangiocarcinoma who received hepatectomies among several clinicopathologic features.…”
Section: Discussionmentioning
confidence: 56%
“…Elevated ALDH activity is also observed in leukemic SC populations in some acute myelogenous leukemia patients (13). ALDH1 serves as a marker of cancer SCs (CSC) in several types of solid tumors, including those of the liver (14), head and neck (15), pancreas (16), lung (17,18), prostate (19), bladder (20), ovary (21), breast (22), and colon (23). On the other hand, the potential of using increased ALDH activities to identify SC subpopulations in cholangiocarcinoma remains to be verified (24).…”
Section: Introductionmentioning
confidence: 99%
“…We next investigated whether altered Stat3 signaling is responsible for the decreased tumorigenicity of ALDH + BCSCs upon deletion of FIP200, as both the BCSC properties and Aldh1a3 levels of ALDH + cells can be regulated by Stat3 signaling (33,34). In FIP200 cKO-MT cells, we observed decreased phospho Stat3 levels (Figure 5A), suggesting that FIP200 is required to sustain Stat3 signaling in PyMT cells.…”
Section: Resultsmentioning
confidence: 99%
“…99 The CD133-or ALDH-positive cells isolated from NSCLC patient samples contain higher levels of the activated form of STAT3. 100 Treatment of these CD133-positive cells with a specific JAK-STAT inhibitor leads to a downregulation of their self-renewal capability as well as a lowering of their resistance to multiple cancer drugs. 100,101 The mechanism underlying STAT3 function in lung CSCs remains to be investigated.…”
Section: Stat3 In Lung Cancer Stem Cellsmentioning
confidence: 99%